Anticytokine Immune Therapy and Atherothrombotic Cardiovascular Risk. Issue 8 (August 2019) - Ait-Oufella, Hafid; Libby, Peter; Tedgui, Alain
Abstract : Accumulating observations in humans and animals indicate that inflammation plays a key role in atherosclerosis development and subsequent complications. Moreover, the use of loss- or gain-of-function genetically modified, atherosclerosis-prone mice has provided strong experimental evidence for a causal role of innate and adaptive immunity in atherosclerosis and has revealed the pathogenic activity of proinflammatory cytokines, including TNF (tumor necrosis factor)-α, IL (interleukin)-1β, IL-6, and IL-18, and the atheroprotective effect of anti-inflammatory cytokines, including IL-10 and TGF-β. For the past 15 years, treatments using monoclonal antibodies specifically targeting cytokines, commonly referred as biological therapies, have transformed the treatment of chronic inflammatory diseases, such as rheumatoid arthritis or psoriasis, both conditions associated with increased cardiovascular risk. Analyzing the impact of anticytokine therapies on the cardiovascular outcomes of patients with chronic inflammatory diseases provides insight into the clinical relevance of experimental data on the role of inflammation in atherothrombotic cardiovascular diseases. CANTOS (Canakinumab Antiinflammatory Thrombosis Outcome Study) provided the first evidence that targeting inflammation in humans with atherosclerosis could improve clinical outcomes. Treatment with the anti–IL-1β antibody canakinumab significantly reduced recurrent cardiovascular events in individuals with stable coronary artery disease well-treated with standard-of-care measures. Other clinical studies support the protective effects of treatment with anti–TNF-α and anti–IL-6 receptor monoclonal antibodies on cardiovascular risk. Blockade of the IL-23/IL-17 axis, however, warrants caution as a cardiovascular intervention. Targeting this pathway has improved psoriasis but may augment cardiovascular risk in certain patients. Thus, careful consideration of the cardiovascular risk profile may influence the choice of the most appropriate treatment for patients with chronic inflammatory diseases.Visual Overview: An online visual overview is available for this article.